Gastric MALT Lymphoma with Giant Ulcer from Untreated H. pylori: Role of Endoscopic Biopsy – A Case Report. - Hysni Dede; Rovena Roshi; Gentiana Cekodhima; Manjola Tahiraj; Augusto Orlandi (Albanian Journal of Trauma and Emergency Surgery)
Introduction: Gastric mucosa-associated lymphoid tissue (MALT) lymphoma is a rare extranodal non-Hodgkin lymphoma strongly linked to Helicobacter pylori infection. It often presents with nonspecific symptoms like dyspepsia, nausea, and epigastric pain and can mimic other gastric pathologies, such as peptic ulcers or gastric cancer.